2011
DOI: 10.1038/jhg.2011.122
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and biochemical characterization of Tunisian patients with glycogen storage disease type III

Abstract: Glycogen storage disease type III (GSD III) is an autosomal recessive inborn error of metabolism caused by mutations in the glycogen debranching enzyme amylo-1,6-glucosidase gene, which is located on chromosome 1p21.2. GSD III is characterized by the storage of structurally abnormal glycogen, termed limit dextrin, in both skeletal and cardiac muscle and/or liver, with great variability in resultant organ dysfunction. The spectrum of AGL gene mutations in GSD III patients depends on ethnic group. The most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Eight genetic diseases belong to this category. This is the case for 11-β hydroxylase deficiency [62,63], hereditary breast and ovarian cancer [64,65], cystic fibrosis [66,67], glycogen storage disease type III [68,69], Leber congenital amaurosis [70], leukocyte adhesion deficiency [71,72] and MDM [Charfeddine C, personal communciation, 37,73]. For some founder mutations, the situation is relatively complex.…”
Section: Resultsmentioning
confidence: 99%
“…Eight genetic diseases belong to this category. This is the case for 11-β hydroxylase deficiency [62,63], hereditary breast and ovarian cancer [64,65], cystic fibrosis [66,67], glycogen storage disease type III [68,69], Leber congenital amaurosis [70], leukocyte adhesion deficiency [71,72] and MDM [Charfeddine C, personal communciation, 37,73]. For some founder mutations, the situation is relatively complex.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, haplotypes are different, indicating that the same mutation occurred independently. In addition, SNP-10 in exon 3 (rs2307130) in Tunisian patient reported by Mili et al [18] was different from patient 12. Also, nonsense mutation p.R1218X (c.3652 CNT) was reported in two patients of Mediterranean origin [20].…”
Section: Discussionmentioning
confidence: 88%
“…A nonsense mutation p.R864X (c.2590CNT) is one of the most prevalent mutations in Caucasian GSD IIIa patients [16] and we found that this mutation is present in a Turkish patient. R864X has been reported in GSD III patients in Italia [17] and Tunisia [18] as well. By using the haplotype study in Chinese and Faroese GSD III patients, Lam et al demonstrated that p.R408X is a recurrent mutation [19].…”
Section: Discussionmentioning
confidence: 96%
“…Phenotypic variation is common among patients with different genotypes who have glycogen storage disease type IIIa. 1,3,11,16,17 In adults, the condition may only be diagnosed late once hepatomegaly, cirrhosis, hepatic carcinoma, cardiomyopathy or neuro-muscular dysfunction has developed. 18 Clinical variability among patients with the same mutation could be related to the age at diagnosis, compliance with dietary recommendations, environment or unknown modifying genes.…”
Section: Discussionmentioning
confidence: 99%